Bast and other plant fibres - Franck, Robert R. (CRC, 2005)
Environmental concerns have regenerated interest in the use of natural fibers for a much wider variety of products, including high-tech applications such as geotextiles, and composite materials for automotive and light industry use. Covering minor as well as major fibers produced worldwide, Bast and Other Plant Fibers analyzes flax, hemp, jute, kenaf, ramie, sisal, coir, and nettle, and provides an index of fiber-yielding plants. Each chapter examining chemical and physical structure, fiber, yarn and fabric production, dying, handle and wear characteristics, economics, and environmental, health and safety issues. A comprehensive set of tables makes it easy to compare the physical and chemical characteristics of different fibers.